Does getting a dog increase recreational walking? - Knuiman Matthew W; Cutt Hayley E; Giles-Corti Billie (BMC, 2008)
Abstract Background This study examines changes in socio-demographic, environmental and intrapersonal factors associated with dog acquisition in non-dog owners at baseline to 12-months follow-up and the effect of dog acquisition on minutes per week of recreational walking. Methods RESIDE study participants completed self-administered questionnaires (baseline and 12-months follow-up) measuring physical activity, dog ownership, dog walking behavior as well as environmental, intrapersonal and socio-demographic factors. Analysis was restricted to 'Continuing non-owners' (i.e., non-owners at both baseline and follow-up; n = 681) and 'New dog owners' (i.e., non-owners who acquired a dog by follow-up; n = 92). Results Overall, 12% of baseline non-owners had acquired a dog at follow-up. Dog acquisition was associated with working and having children at home. Those who changed from single to couple marital status were also more likely to acquire a dog. The increase in minutes of walking for recreation within the neighborhood from baseline to follow-up was 48 minutes/week for new dog owners compared with 12 minutes/week for continuing non-owners (p < 0.05). After adjusting for baseline variables the effect of dog acquisition on the increase in minutes of recreational walking within the neighborhood was 31 minutes (95% CI: 7.39, 54.22; p < 0.01). However, this reduced to 22 minutes (95% CI: -1.53, 45.42; p > 0.05) after further adjustment for change in baseline to follow-up variables. Increase in intention to walk was the main factor contributing to attenuation of the effect of dog acquisition on recreational walking. Conclusion This study used a large representative sample of non-owners to examine the relationship between dog acquisition and recreational walking and provides evidence to suggest that dog acquisition leads to an increase in walking. The most likely mechanism through which dog acquisition facilitates increased physical activity is through behavioral intention via the dog's positive effect on owner's cognitive beliefs about walking, and through the provision of motivation and social support for walking. The results suggest that behavioral intention mediates the relationship between dog acquisition and walking and that dogs may have a significant role in the maintenance of owner walking behavior.